Zircon U–Pb isotopes and trace element data from samples in the Majorqaq Belt, Greenland - Ni, Ziqin; Arevalo Jr, Ricardo; Piccoli, Philip; Reno, Barry (IEDA: EarthChem Library, 2020)
Abstract: This dataset contains LA-ICP-MS results of U-Pb and trace element data from metasedimentary rocks that were sampled from the Majorqaq Belt, southern West Greenland. Other Description: Ni, Z. Arevalo, R. J., Piccoli, P., Reno B., A novel approach to identifying mantle-equilibrated zircon by using trace element chemistry, Geochemistry, Geophysics, Geosystems (accepted) Dyck, B., Reno, B.L., Kokfelt, T.F., 2015. The Majorqaq Belt: A record of Neoarchaean orogenesis during final assembly of the North Atlantic Craton, southern West Greenland. Lithos 220–223, 253–271. https://doi.org/10.1016/j.lithos.2015.01.024